Antimicrobial modification of PLA scaffolds with ascorbic and fumaric acids via plasma treatment - Anton Popelka (2804842) (2020)
An optimal medical scaffold should be biocompatible and biodegradable and should have adequate mechanical properties and scaffold architecture porosity, a precise three-dimensional shape, and a reasonable manufacturing method. Polylactic acid (PLA) is a natural biodegradable thermoplastic aliphatic polyester that can be fabricated into nanofiber structures through many techniques, and electrospinning is one of the most widely used methods. Medical fiber mat scaffolds have been associated with inflammation and infection and, in some cases, have resulted in tissue degradation. Therefore, surface modification with antimicrobial agents represents a suitable solution if the mechanical properties of the fiber mats are not affected. In this study, the surfaces of electrospun PLA fiber mats were modified with naturally occurring l-ascorbic acid (ASA) or fumaric acid (FA) via a plasma treatment method. It was found that 30 s of radio-frequency (RF) plasma treatment was effective enough for the wettability enhancement and hydroperoxide formation needed for subsequent grafting reactions with antimicrobial agents upon their decomposition. This modification led to changes in the surface properties of the PLA fiber mats, which were analyzed by various spectroscopic and microscopic techniques. FTIR-ATR confirmed the chemical composition changes after the modification process and the surface morphology/topography changes were proven by SEM and AFM. Moreover, nanomechanical changes of prepared PLA fiber mats were investigated by AFM using amplitude modulation-frequency modulation (AM-FM) technique. A significant enhancement in antimicrobial activity of such modified PLA fiber mats against gram-positive Staphylococcus aureus and gram-negative Escherichia coli are demonstrated herein. Other Information Published in: Surface and Coatings Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.surfcoat.2020.126216